Understanding Marsha Norman - Tyler, Lisa, 1964- (Understanding contemporary American literature., 2019)
"Perhaps prompted by an interviewer's question (Beattie 292), American playwright Marsha Norman has described 'trapped girls' as an important theme of her work, one that stems from her own childhood experiences growing up in a fundamentalist Christian family: 'I saw myself as a trapped girl as a kid ... trapped in this evangelical household full of violence' (Myers). Her mother, a fundamentalist Methodist, had a violent temper and strong religious beliefs. She forbade her children to watch television because of its perceived sinfulness, so Marsha spent much of her childhood reading. 'I had a very isolated childhood, read a lot, played a lot and wasn't allowed to frown, ' Norman has said (Brustein 184). She often felt trapped in a hostile environment and later recalled longing to be kidnapped so that she could escape her family. Norman identifies the theme of the trapped girl not only in the character of Arlie in her first play, Getting Out, and Jessie in 'night, Mother, but also in Mary Lennox in The Secret Garden, Celie Johnson in The Color Purple, and Francesca Johnson in The Bridges of Madison County"--